Point-prevalence surveys of antimicrobial consumption and resistance at a paediatric and an adult tertiary referral hospital in Yangon, Myanmar. Issue 1 (March 2022) - Oo, Win Thandar; Carr, Samuel D.; Marchello, Christian S.; San, Moe Moe; Oo, Aung Tun; Oo, Khine Mar; Lwin, Kay Thi; Win, Hla Hla; Crump, John A.
Summary: Background: Antimicrobial resistance is increasingly prevalent worldwide. The inappropriate use of antimicrobials, including in the hospital setting, is considered a major driver of antimicrobial resistance. Aim: To inform improvements in antimicrobial stewardship, we undertook point prevalence surveys of antimicrobial prescribing at Yangon Children's Hospital and Yangon General Hospital in Yangon, Myanmar. Methods: We conducted our surveys using the Global Point-Prevalence Survey of Antimicrobial Consumption and Resistance (Global-PPS) method. All inpatients who were prescribed an antimicrobial on the day of the survey were included in the analysis. Findings: We evaluated a total of 1, 980 patients admitted to two hospitals during December 2019. Of these, 1, 255 (63.4%) patients were prescribed a total of 2, 108 antimicrobials. Among antimicrobials prescribed, 722 (34.3%) were third-generation cephalosporins, the most commonly prescribed antimicrobial class. A total of 940 (44.6%) antimicrobials were prescribed for community-acquired infection, and 724 (34.3%) for surgical prophylaxis. Of 2, 108 antimicrobials, 317 (15.0%) were prescribed for gastrointestinal tract prophylaxis, 305 (14.5%) for skin, soft tissue, bone and joint prophylaxis, and 303 (14.4%) for pneumonia treatment. A stop or review date was documented for 350 (16.6%) antimicrobial prescriptions, 673 (31.9%) antimicrobial prescriptions were guideline compliant, and 1, 335 (63.3%) antimicrobials were administered via the parenteral route. Of 1, 083 antimicrobials prescribed for a therapeutic use, 221 (20.4%) were targeted therapy. Conclusion: Our findings underscore the need to update and expand evidence-based guidelines for antimicrobial use, promote the benefits of targeted antimicrobial therapy, and support the implementation of hospital-based antimicrobial stewardship programmes at the hospitals surveyed.